T cell stimulation by staphylococcal enterotoxins. Clonally variable response and requirement for major histocompatibility complex class II molecules on accessory or target cells (The Rockefeller University Press, 1988)
Staphylococcal enterotoxins (SE) are the most potent mitogens for T lymphocytes known; concentrations of less than 10(-9) M are sufficient for T cell activation. The mechanism of T cell activation by SE is unknown. We have used cloned human cytotoxic and proliferative T lymphocytes to dissect the molecular mechanism of T cell activation by SE. With rare exceptions, all TCR alpha/beta chain-expressing T cell clones of CD4+ or CD8+ phenotype, as well as CD4-8- TCR alpha/beta chain negative chain-expressing T lymphocyte clones, respond with proliferation and/or cytotoxicity to SE. For triggering of all these clones, the presence of autologous or allogeneic MHC class II molecules on accessory or target cells is necessary. This requirement for class II antigens is not due to an immunological recognition of processed SE, since inhibition of antigen processing has no influence on the T cell response to SE. SE acts on the T cells directly since (a) they stimulate a rise in intracellular calcium concentration in T cell lines or purified T cells, and (b) accessory cells can be replaced by phorbolesters in the proliferative activation of resting T cells by SE. Furthermore, the T cell response to SE shows extensive clonal heterogeneity. These results suggest that SE are functionally bivalent mitogens binding highly selectively to HLA class II molecules and the TCR. Thus, compared with other polyclonal T cell activating agents, activation with SE most closely mimicks the physiological way of MHC- restricted antigen recognition by T lymphocytes.